Inclusive teaching in South Africa - Makoelle, Tsediso Michael (SUN MeDIA under the SUN Press imprint, 2016)
Inclusive education presupposes an all-inclusive approach where all learners are taught in regular classrooms, regardless of background, disability or social context. While there has been much debate, indications are that inclusive education has been gaining momentum. The book is divided into six coherent sections that address the how of inclusive education both inside and outside of the classroom--Publisher's website